(3GdWGQbjIs - (3GHf NGdhjg , GdMSjf Hf CMeO Hf NGdhjg Hf MeOGf, CHh YHO Gddg,J (B370 (3g` s ((3efUhQ Hf SYjO GdeZQHj GdTgjQ HGHf Rjf GdCRgQj s)
(3ChdgG (B:s
(3bGd CHhYHOGddg gPG cJGH PcQJ ajg EYQGH KdGKjf ShQI HTQM eYGfj cd MQa hJdNjU aQhYg s
(3BNQgG (B:s
(3adPdc bGd(B: (3ef GdLfI LQ Hef hGdfGS fSb Ydjg fLRJ GdWGQbjI s
(3ajg VHWs
(3eged GdfbW CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs